The Role of Opinion Leaders in Bullying Prevention: Evaluating the Roots Program in SMA Negeri 19 Medan Through the Lens of Two-Step Flow Communication Theory - Dalimunthe, Maulana Andinata; Ritonga, Aulia Rahma; Ananda, Sofiari (Komunika, 2025)
This study aims to assess the effectiveness of the Roots Program in preventing bullying through the lens of the Two-Step Flow Communication Theory, emphasizing the role of student opinion leaders in influencing peer behavior and fostering a safer school environment. A qualitative research approach with an analytical descriptive method was used. Data were collected through in-depth interviews with three key informants: the school principal, a teacher facilitator, and a student anti-bullying agent. The findings indicate that the Roots Program has contributed to a noticeable reduction in bullying incidents by leveraging peer influence. Student opinion leaders played a crucial role in shaping anti-bullying norms through peer discussions, advocacy, and social modeling. The research highlights that students are more receptive to anti-bullying messages delivered by peers rather than institutional authorities, aligning with the Two-Step Flow Communication Theory. However, challenges such as ensuring active student participation and overcoming reluctance to report bullying remain significant obstacles. The study also found that institutional support, including teacher facilitation and collaboration with external organizations, enhances the effectiveness of peer-led interventions.